Criminal Limitations on Diversion of Children Against the Law Based on the Juvenile Criminal Justice System from a Comparative Perspective - Ananta, Ahmad Rizal Roby; Wicaksono, Demas Brian; Berliansyah, Devi Tri; Lestari, Dewi (Jurnal Penegakan Hukum dan Keadilan, 2025)
This research explores the protection of children’s rights within the criminal justice system, with a particular focus on the legal constraints surrounding the use of diversion for children in conflict with the law (ABH), as regulated by Law Number 11 of 2012 on the Juvenile Criminal Justice System (SPPA). While the Indonesian Constitution and international legal frameworks—such as the Convention on the Rights of the Child (CRC), ratified through Presidential Decree Number 36 of 1990—guarantee these rights, challenges persist in their implementation, especially during legal proceedings. The study employs a normative legal method, incorporating comparative and conceptual approaches, by examining how Indonesia’s diversion system compares with Finland’s and Sweden’s. The findings indicated that despite Indonesia’s adoption of restorative justice principles in the  Sistem Peradilan Pidana Anak (CJSC), the practical application of diversion remains hindered by several factors. These include a lack of understanding among legal practitioners, inadequate rehabilitation facilities, and limited victim involvement in resolving cases. Furthermore, the restriction of diversion to crimes carrying sentences of less than seven years fails to fully uphold the principle of prioritizing the child’s best interests. While earlier research has analyzed diversion in terms of recidivism rates and law enforcement implementation, this study emphasizes the principle of non-discrimination within Indonesia’s juvenile justice system. As a result, the study advocates for more comprehensive policy reforms to broaden the scope of diversion, better align with restorative justice principles, and ensure stronger protection for children entangled in legal conflicts.